Apakah Pengeluaran Pemerintah Mendorong Keberlanjutan Lingkungan? Bukti dari Emisi Karbon di Indonesia: Does Government Expenditure Promote Environmental Sustainability? Evidence from Carbon Emissions in Indonesia - Azwar Azwar; Bayu Taufiq Possumah (AMANAH: Jurnal Manajemen Keuangan Sektor Publik, 2026)
This study aims to examine the effect of government expenditure on carbon emissions in Indonesia using a quantitative econometric approach. Specifically, it aims to identify the direction and significance of the relationship between public spending and environmental outcomes, thereby providing empirical insights for aligning fiscal policy with sustainable development objectives. The study employs a multiple linear regression model based on annual time-series data covering the period 2000–2024. The data are obtained from the World Bank’s World Development Indicators (WDI), particularly the reporting period for national accounts data. The empirical results indicate that government expenditure has a negative and statistically significant effect on carbon emissions, suggesting that higher public spending may contribute to environmental improvement when allocated toward environmentally supportive sectors such as green infrastructure and efficient public services. Urbanization, however, shows a positive and significant relationship with carbon emissions, implying that urban growth in Indonesia remains associated with energy-intensive economic activities. Meanwhile, GDP does not exhibit a statistically significant effect, which may indicate a potential decoupling between economic growth and environmental degradation, although the evidence remains inconclusive. Energy use intensity shows a negative but statistically insignificant effect on carbon emissions. The findings suggest that fiscal policy can serve as a strategic instrument to support environmental sustainability when integrated with green economic policies and energy transition strategies.